Clinical burden of Acinetobacter baumannii, including carbapenem-resistant A. baumannii, in hospitalized adult patients in the USA between 2018 and 2022 - Thomas P. Lodise; Sean T. Nguyen; Caroline Margiotta; Bin Cai (BMC Infectious Diseases)
Abstract Background Epidemiological data for United States (US) hospitals regarding the burden of Acinetobacter baumannii and carbapenem-resistant A. baumannii (CRAB) are scarce; thus, this study aimed to describe the incidence of A. baumannii and CRAB across US hospitals between January 1, 2018 and December 31, 2022. Methods This was a retrospective cohort study of hospitalized patients with microbiology data from the PINC AI™ Database. Incidence rates of A. baumannii and CRAB (January 1, 2018 – December 31, 2022) were determined across US hospitals in each census region. Incidence rates of A. baumannii and CRAB were determined at the hospitalization encounter and individual levels. Presence of CRAB was based on non-susceptibility to either doripenem, imipenem, or meropenem. Patient demographics, comorbidities, outcomes, including in-hospital mortality, were compared between patients with CRAB and carbapenem-susceptible A. baumannii (CSAB) at the hospitalization encounter level. Results During the study period, 7,270 hospitalization encounters with ≥ 1 A. baumannii clinical cultures were identified. The overall A. baumannii incidence rate was 1.19 cases per 100 hospitalization encounters and 1.33 cases per 100 unique patients. For CRAB, a total of 2,708 hospitalization encounters were identified, and incidence rate was 0.44 cases per 100 hospitalization encounters. The West South Central, East North Central, and East South Central regions had the highest CRAB incidence rates (0.78, 0.67, and 0.63 cases per 100 hospitalization encounters, respectively). Compared with CSAB, patients with CRAB had significantly more positive cultures with A. baumannii (20.9% vs. 10.0%, respectively, P < 0.0001) and higher prevalence of other Gram-negative pathogens in any clinical culture site within ± 3 days of the index A. baumannii clinical culture (47.2% vs. 42.9%, respectively, P = 0.0004). Patients with CRAB had higher incidences of in-hospital mortality vs. patients with CSAB (20.5% vs. 11.3%, respectively, P < 0.0001). Conclusions Presence of A. baumannii was identified on a clinical culture in 1% of adult hospitalizations in this multicenter US study. Over a third of A. baumannii hospitalization encounters were CRAB, with the highest incidence rates per 100 hospitalization encounters observed in the most central US regions. Clinicians should consider A. baumannii as a potential pathogen in patients in regions with an increasing incidence rate of A. baumannii.